Growth of Neanderthal infants from Krapina (120–130 ka), Croatia. Issue 1963 (24th November 2021) - Mahoney, Patrick; McFarlane, Gina; Smith, B. Holly; Miszkiewicz, Justyna J.; Cerrito, Paola; Liversidge, Helen; Mancini, Lucia; Dreossi, Diego; Veneziano, Alessio; Bernardini, Federico; Cristiani, Emanuela; Behie, Alison; et al.
Abstract : Modern humans have a slow and extended period of childhood growth, but to what extent this ontogenetic pathway was present in Neanderthals is debated. Dental development, linked to the duration of somatic growth across modern primates, is the main source for information about growth and development in a variety of fossil primates, including humans. Studies of Neanderthal permanent teeth report a pace of development either similar to recent humans or relatively accelerated. Neanderthal milk teeth, which form and emerge before permanent teeth, provide an opportunity to determine which pattern was present at birth. Here we present a comparative study of the prenatal and early postnatal growth of five milk teeth from three Neanderthals (120 000–130 000 years ago) using virtual histology. Results reveal regions of their milk teeth formed quickly before birth and over a relatively short period of time after birth. Tooth emergence commenced towards the earliest end of the eruption schedules displayed by extant human children. Advanced dental development is consistent with expectations for Neanderthal infant feeding.